2020
DOI: 10.1111/jphp.13320
|View full text |Cite
|
Sign up to set email alerts
|

The effect of apatinib on pharmacokinetic profile of buspirone both in vivo and in vitro

Abstract: Objective In this study, we aimed to investigate the potential interaction of apatinib and buspirone and underlying mechanism. Methods UPLC‐MS/MS assay was applied to determine the concentrations of buspirone and its main metabolites (1‐PP and 6‐OH buspirone) after incubated with liver microsomes. Moreover, the connection of in vitro and in vivo was further determined. Sprague Dawley rats were randomly divided into two groups: group A (20 mg/kg buspirone) and group B (buspirone vs 40 mg/kg apatinib). Tail vein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Therefore, combining apatinib with fluvoxamine is an effective dosing strategy. Many studies had shown that apatinib interacts with antipsychotics like buspirone and venlafaxine (Bao et al, 2018;Zhang et al, 2020). In this study, the data demonstrated that it can also inhibit the metabolizing of fluvoxamine via suppression the activities of microsomes system, especially CYP2D6.…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, combining apatinib with fluvoxamine is an effective dosing strategy. Many studies had shown that apatinib interacts with antipsychotics like buspirone and venlafaxine (Bao et al, 2018;Zhang et al, 2020). In this study, the data demonstrated that it can also inhibit the metabolizing of fluvoxamine via suppression the activities of microsomes system, especially CYP2D6.…”
Section: Discussionmentioning
confidence: 62%
“…Previous laboratory experiments have shown that icotinib has an inhibitory effect on CYP3A ( Zhang et al, 2018 ). Moreover, it has been reported that apatinib inhibits the activity of cytochrome P450 enzymes ( Bao et al, 2018 ; Zhang et al, 2020 ). To further investigate this aspect, we conducted in vitro experiments using RLMs and HLMs.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also shortcomings in the biological treatment process. Skin inflammation, hypertension, gastrointestinal reactions, proteinuria, cytopenias, hand-foot syndrome, abdominal pain, and abdominal distension often occur during treatment, which can be alleviated by symptomatic supportive treatment [ 58 ]. It’s been reported that Apatinib is well tolerated and very effective in the treatment of advanced HCC, and it is beneficial in terms of objective remission rate and disease control rate [ 59 ].…”
Section: Discussionmentioning
confidence: 99%